2023
DOI: 10.11591/edulearn.v17i2.20782
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ex-add learning techniques on critical thinking skills and pedagogic competence of Islamic education students

Abstract: This study aimed to determine the effect of explain-analysis-doing-discussion or known as ex-add learning techniques on critical thinking skills and pedagogic competence of Islamic religious education students at State Islamic University (UIN) Sulthan Thaha Saifuddin Jambi and at UIN Raden Fatah Palembang, Indonesia. The approach used quantitative with quasi-experimental techniques. The number seen in this study was 31 students from UIN Sulthan Thaha Saifuddin Jambi. The data were obtained using tests, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Based on the National Higher Education Standards in the fourth part of the learning process standards, one of the characteristics of the learning process as in article 10 paragraph (2) letter a is contextual. According to Mahfudz & Sukarno (2023) in his research he found that the Contextual Teaching and Learning approach was able to improve cognitive competence and 21st century skills competence.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the National Higher Education Standards in the fourth part of the learning process standards, one of the characteristics of the learning process as in article 10 paragraph (2) letter a is contextual. According to Mahfudz & Sukarno (2023) in his research he found that the Contextual Teaching and Learning approach was able to improve cognitive competence and 21st century skills competence.…”
Section: Resultsmentioning
confidence: 99%
“…, 2023; Kurniawan et al. , 2023, Mahfudz and Sukarno, 2023; Putkonen and Poulter, 2023; R’boul et al. , 2023; Suharsongko et al.…”
Section: Methodsmentioning
confidence: 99%
“…In the first phase, education literature and previous studies related to the features of IE teachers (e.g. Abdullah et al, 2023;Kurniawan et al, 2023, Mahfudz andSukarno, 2023;Putkonen and Poulter, 2023;R'boul et al, 2023;Suharsongko et al, 2023;Tuna et al, 2023) were reviewed to propose items representing the components of standards for candidates. These items were formulated into a questionnaire, which was conducted according to the Delphi method in three rounds, in which a committee of experts in of IE participated (Zartha Sossa et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Mengingat demikian pentingnya peranan Al-Qur'an dalam kehidupan manusia maka kemampuan membaca Al-Qur'an yang baik dan benar (fasih) juga merupakan bagian terpenting dalam pendidikan Islam (Mardiana & Anggraini, 2019). Oleh karena itu, salah satu tolak ukur yang bisa digunakan untuk menilai kesadaran masyarakat dalam mempelajari dan mengamalkan ajaran-ajaran Islam serta menilai kondisi pendidikan Islam adalah kemampuan anak-anak dalam membaca Al-Qur'an (Mahfudz & Sukarno, 2023).…”
Section: Pendahuluanunclassified